2002
DOI: 10.1002/j.1556-6678.2002.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

One Family at a Time: A Prevention Program for At‐Risk Parents

Abstract: The purpose of this study was to examine the effectiveness of a psychoeducational parenting program with at‐risk parents of young children. At‐risk was defined as excessive parental use of verbal and corporal punishment combined with low‐income status. All families were seen for 10 weeks, either individually or in very small groups. Results showed that compared with the control group, parents participating in the program significantly decreased their levels of verbal and corporal punishment, anger, stress, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
1
13

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 40 publications
(36 reference statements)
1
87
1
13
Order By: Relevance
“…Specifically, only mothers were recruited for 13 studies (Chronis et al, 2006;DeGarmo et al, 2004;Farrar et al, 2005;Feliciana, 2005;Gammon & Rose, 1991;Greaves, 1997;Gutierrez, 2007;Hiscock et al, 2008;Lipman & Boyle, 2005;Niccols, 2009;Odom, 1996;Sirbu, Cotler, & Penman, 1978;Wolfe & Hirsch, 2003). Some exceptions existed in that four studies recruited not only biological parents but also grandparents, foster parents, stepparents, and relatives (Gross et al, 2003;Gross et al, 2009;Nicholson, Anderson, Fox, & Brenner, 2002;Treacy et al, 2005). Both mothers and fathers were recruited in 19 studies (Blakemore et al, 1993;Fanning, 2007;Gross, Fogg, & Tucker, 1995;Hanisch et al, 2010;Hutchings et al, 2007;Irvine, Biglan, Smolkowski, Metzler, & Ary, 1999;Larsson et al, 2009;Matsumoto et al, 2007;Matsumoto et al, 2010;McGillicuddy, Rychtarik, Duquette, & Morsheimer, 2001;Nixon & Singer, 1993;Pisterman et al, 1992a;Pisterman et al, 1992b;Schultz et al, 1993;Taylor et al, 1998;van den Hoofdakker et al, 2007;Wang, 2005;Webster-Stratton, Kolpacoff, & Hollinsgworth, 1988;Wolfson et al, 1992).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, only mothers were recruited for 13 studies (Chronis et al, 2006;DeGarmo et al, 2004;Farrar et al, 2005;Feliciana, 2005;Gammon & Rose, 1991;Greaves, 1997;Gutierrez, 2007;Hiscock et al, 2008;Lipman & Boyle, 2005;Niccols, 2009;Odom, 1996;Sirbu, Cotler, & Penman, 1978;Wolfe & Hirsch, 2003). Some exceptions existed in that four studies recruited not only biological parents but also grandparents, foster parents, stepparents, and relatives (Gross et al, 2003;Gross et al, 2009;Nicholson, Anderson, Fox, & Brenner, 2002;Treacy et al, 2005). Both mothers and fathers were recruited in 19 studies (Blakemore et al, 1993;Fanning, 2007;Gross, Fogg, & Tucker, 1995;Hanisch et al, 2010;Hutchings et al, 2007;Irvine, Biglan, Smolkowski, Metzler, & Ary, 1999;Larsson et al, 2009;Matsumoto et al, 2007;Matsumoto et al, 2010;McGillicuddy, Rychtarik, Duquette, & Morsheimer, 2001;Nixon & Singer, 1993;Pisterman et al, 1992a;Pisterman et al, 1992b;Schultz et al, 1993;Taylor et al, 1998;van den Hoofdakker et al, 2007;Wang, 2005;Webster-Stratton, Kolpacoff, & Hollinsgworth, 1988;Wolfson et al, 1992).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Nineteen studies evaluated the effectiveness of a cognitive-behavioral parenting program (Blakemore et al, 1993;Chronis et al, 2006;Gammon Rose, 1991;Gardner et al, 2006;Greaves, 1997;Gross et al, 1995;Gross et al, 2003;Gross et al, 2009;Hutchings et al, 2007;Joyce, 1995;Larsson et al, 2009;Lipman & Boyle 2005;McGillicuddy et al, 2001;Nicholson et al, 2002;Nixon & Singer, 1993;Patterson et al, 2002;Spaccerelli et al, 1992;Taylor et al, 1998;Webster Stratton et al,1988). These programs combined the basic behavioral-type strategies with cognitive strategies aimed at helping parents to identify and change distorted patterns of belief or thought that might be influencing their behavior.…”
Section: Cognitive-behavioral Parenting Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported the efficacy of the PYC model for young children with behavior problems, notably including at-risk children living in poverty Nicholson, Anderson, Fox, & Brenner, 2002), children with developmental delays (Holtz, Carrasco, Mattek, & Fox, 2009) and children from different ethnic backgrounds (Gresl, Fox, & Fleischmann, in press). In addition, a mental health clinic providing in-home PCT services to at-risk children with developmental delays and severe behavior problems has reported successful treatment outcomes for the past decade (Fox, Keller, Grede, & Bartosz, 2007).…”
mentioning
confidence: 99%
“…These early intervention programs, which consist largely of cognitive-behavioral procedures that are developmentally appropriate for toddlers and preschoolers, have significantly reduced early childhood behavior problems (Brinkmeyer & Eyberg, 2003;Nicholson, Anderson, Author, & Brenner, 2002;Webster-Stratton, 1994). The treatment efficacy research for these early intervention programs is relatively new and initial studies have been conducted in well-controlled, laboratory or clinic-based studies (Lyon & Budd, 2010).…”
mentioning
confidence: 99%